The Role of Anatomical Education in Medical Curriculum Reforms: Impact on Public Health, Orthopaedic Surgical Practice, and Radiological Diagnosis - Shehla Farhin, Muhammad Azhar Khan, Sara Bano, Huma Beenish, Muhammad Yousuf Memon, Syeda Ayesha Alam (Pakistan Journal of Medical & Health Sciences, 2023)
Background: Anatomy forms the foundation of all medical sciences and serves as a bridge between basic knowledge and clinical application. However, contemporary curriculum reforms across medical schools have led to a reduction in dedicated anatomy teaching hours, limited dissection exposure, and an overreliance on digital learning. These changes have raised concerns regarding declining clinical competence, particularly in surgical precision, diagnostic interpretation, and public health practice. This study aimed to evaluate the role of anatomical education within reformed curricula and its impact on public health outcomes, orthopaedic surgical practice, and radiological diagnosis. Materials and Methods: A descriptive cross-sectional study was conducted at the Departments of Anatomy, Bakhtawar Amin Medical and Dental College, Multan, and Al-Nafees Medical College and Hospital, Islamabad, from January 2022 to March 2023. A total of 100 participants, including anatomy faculty, orthopaedic surgeons, and radiologists, were selected using purposive sampling. Data were collected through structured questionnaires and semi-structured interviews focusing on the perceived relevance of anatomical education in clinical practice. Statistical analysis was performed using SPSS version 25, applying descriptive and inferential methods, while qualitative data were thematically analyzed. Results: Out of 100 participants, 82% acknowledged anatomy as essential for linking basic and clinical sciences. Ninety percent (90%) of orthopaedic surgeons reported that comprehensive anatomical knowledge improves surgical precision and minimizes complications. Similarly, 87% of radiologists emphasized that strong anatomical understanding enhances diagnostic accuracy. In public health, 78% agreed that anatomical literacy supports preventive strategies and community-based interventions. However, 84% of respondents expressed dissatisfaction with the current anatomy curriculum, citing decreased dissection time and insufficient clinical integration. Surgeons with high anatomical proficiency showed a significantly lower surgical error rate (2.1%) compared to those with poor proficiency (11.4%) (p < 0.05). Conclusion: Anatomical education remains vital for safe and effective medical practice. Strengthening anatomy within reformed curricula through hybrid teaching—combining traditional cadaveric dissection with 3D visualization and radiological integration—can enhance clinical competence, surgical accuracy, and diagnostic efficiency. Reestablishing anatomy as a clinically oriented discipline is essential to improve both public health outcomes and patient safety in modern medical practice. Keywords: Anatomy, Medical Education Reform, Public Health, Orthopaedic Surgery, Radiological Diagnosis, Dissection, Curriculum Integration, Clinical Competence